The bridge battle - Davies, Jacqueline, 1962- (Davies, Jacqueline, 1962- Lemonade war series, 2022)
Siblings Evan and Jessie Treski are surprised when they find themselves in unfamiliar waters during summer vacation. Evan has never had trouble making friends before, but he struggles when he falls prey to a bully on the playground during summer school. Jessie is ready construct the best bridge she can for an upcoming competition, but she is horrified when she is placed in the wrong summer camp, surrounded by kids who believe fairies are more real than physics. The two siblings must find a way to survive these strange, new experiences.